Markers of systemic and gut-specific inflammation in celiac disease - Palumbo, Chiara Saroli; Wyse, Jonathan (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Saroli Palumbo C, Wyse J. Markers of systemic and gut-specific inflammation in celiac disease. Turk J Gastroenterol 2020; 31(2): 187-9.